A Concept for Preoperative and Intraoperative Molecular Imaging and Detection for Assessing Extent of Disease of Solid Tumors - Hitchcock, Charles L.; Chapman, Gregg J.; Mojzisik, Cathy M.; Mueller, Jerry K.; Martin, Edward W. (Oncology Reviews, 2024)
The authors propose a concept of “systems engineering,” the approach to assessing the extent of diseased tissue (EODT) in solid tumors. We modeled the proof of this concept based on our clinical experience with colorectal carcinoma (CRC) and gastrinoma that included short and long-term survival data of CRC patients. This concept, applicable to various solid tumors, combines resources from surgery, nuclear medicine, radiology, pathology, and oncology needed for preoperative and intraoperative assessments of a patient’s EODT. The concept begins with a patient presenting with biopsy-proven cancer. An appropriate preferential locator (PL) is a molecule that preferentially binds to a cancer-related molecular target (i.e., tumor marker) lacking in non-malignant tissue and is the essential element. Detecting the PL after an intravenous injection requires the PL labeling with an appropriate tracer radionuclide, a fluoroprobe, or both. Preoperative imaging of the tracer’s signal requires molecular imaging modalities alone or in combination with computerized tomography (CT). These include positron emission tomography (PET), PET/CT, single-photon emission computed tomography (SPECT), SPECT/CT for preoperative imaging, gamma cameras for intraoperative imaging, and gamma-detecting probes for precise localization. Similarly, fluorescent-labeled PLs require appropriate cameras and probes. This approach provides the surgeon with real-time information needed for R0 resection.